A Simple and Sensitive HPLC-MS/MS Assay for the Quantitation of Blonanserin and N-Desethyl Blonanserin in Rat Plasma and Its Application to Pharmacokinetic Study. (7th April 2022) - Huang, Shan-qing; Li, Xiao-lin; Wang, Zhan-zhang; Lu, Hao-yang; Xiao, Tao; Ni, Xiao-jia; Liu, Shu-jing; Zhang, Ming; Shang, De-wei; Wen, Yu-guan
Abstract : A high-performance liquid chromatographic method coupled with triple quadrupole mass spectrometry (LC-MS/MS) for the analysis of blonanserin and its active metabolite, N -desethyl blonanserin, in rat plasma has been developed and validated. The biological samples were treated by simple direct protein precipitation before separation on an Agilent Eclipse Plus C18 column (4.6 × 100 mm, 3.5  μ m) with a column temperature of 35°C at a flow rate of 0.5 mL/min. The mobile phase A is a mixture of methanol and water (75 : 25, v/v, 5 mM ammonium formate), and the mobile phase B is acetonitrile containing 0.1% formic acid. The ratio of mobile phase A to mobile phase B is 15 : 85. Electrospray ionization (ESI) multiple reaction monitoring modes are used for detection, which are m/z 368.10 ⟶ 296.90 (blonanserin), m/z 340.15 ⟶ 297.05( N -desethyl blonanserin), and m/z 348.15⟶ 302.05 ( N -desethyl blonanserin-d8 ). The linear response range was 0.1–100.0 ng/mL for blonanserin and N -desethyl blonanserin. The lower limit of quantification (LLOQ), calibration curves, carryover, and matrix effects were sufficiently accurate and precise according to the National Medical Products Administration (NMPA) guidelines for bioanalytical method validation. This analytical method was successfully applied in a blonanserin-poloxamer thermosensitive gel pharmacokinetic study in rats.